The determination of antioxidant and antimicrobial analysis of Gaharu essential oil and Gaharu leaves in soap formulations: article / Mohamad Afiq Ikhwan Mohd Noor Velan and Habsah Alwi - Mohd Noor Velan, Mohamad Afiq Ikhwan; Alwi, Habsah (2019)
In this study, the new utilization of Gaharu main components which is Gaharu essential oil and Gaharu leaves was conducted by integration into the soap formulation. Six different soap formulation were prepared using hot process soap making. The analysis in the soap performance was conducted on the soap stability such as appearance attribute, pH and foaming ability. Furthermore, antioxidant and antibacterial abilities was conducted using 2,2DiphenylPicrylHydrazyl (DPPH) assays and Kirby Bauer Disk Diffusion assay were co respectively. These studies show that the soap samples added with Gaharu essential oil provides a good soap attribute such as appearance, odor and good antioxidant activity while the soap samples added with Gaharu leaves yield no added attribute such as good odor and pleasant appearance but possess a good antioxidant free radical scavenging activity of 71.83 percent radical scavenging activity. The antimicrobial analysis shows highest inhibition for coconut soap added with Gaharu essential oil of 14 mm, while there is no inhibition of olive soap samples even with addition of Gaharu essential oil.